2007
DOI: 10.1186/1471-2229-7-54
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic xylan-binding modules for mapping of pulp fibres and wood sections

Abstract: Background: The complex carbohydrate composition of natural and refined plant material is not known in detail but a matter that is of both basic and applied importance. Qualitative assessment of complex samples like plant and wood tissues requires the availability of a range of specific probes. Monoclonal antibodies and naturally existing carbohydrate binding modules (CBMs) have been used in the past to assess the presence of certain carbohydrates in plant tissues. However, the number of natural CBMs is limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…From enzymatic degradation of cell walls using xylanase, Parameswaran and Sinner (1979) and Parameswaran and Liese (1982) also showed the distribution of xylan in cell walls. More recently, cytochemical studies have shown the distribution of xylans in wood cell walls using various immunological probes such as xylanase-gold complexes, antibodies, and carbohydrate binding modules (Awano et al 1998(Awano et al , 2000(Awano et al , 2002Carafa et al 2005;Filonova et al 2007;Hosoo et al 2006;Ruel et al 2006;Vian et al 1986Vian et al , 1992. In particular, Awano et al (1998Awano et al ( , 2000Awano et al ( , 2002 systematically investigated the distribution of xylans (AcGXs) in the cell walls of fibers using various immunological methods in combination with enzyme and chemical treatment of the cell walls.…”
Section: Introductionmentioning
confidence: 99%
“…From enzymatic degradation of cell walls using xylanase, Parameswaran and Sinner (1979) and Parameswaran and Liese (1982) also showed the distribution of xylan in cell walls. More recently, cytochemical studies have shown the distribution of xylans in wood cell walls using various immunological probes such as xylanase-gold complexes, antibodies, and carbohydrate binding modules (Awano et al 1998(Awano et al , 2000(Awano et al , 2002Carafa et al 2005;Filonova et al 2007;Hosoo et al 2006;Ruel et al 2006;Vian et al 1986Vian et al , 1992. In particular, Awano et al (1998Awano et al ( , 2000Awano et al ( , 2002 systematically investigated the distribution of xylans (AcGXs) in the cell walls of fibers using various immunological methods in combination with enzyme and chemical treatment of the cell walls.…”
Section: Introductionmentioning
confidence: 99%
“…Altaner et al (2010) have examined the distribution of heteroxylans in radiata pine (Pinus radiata) by immunoelectron microscopy showing unsubstituted xylans (LM10) in the S1 and S3 layers and more highly substituted xylans (LM11) across all areas of the cell wall except the primary wall. Filonova et al (2007) also demonstrated a generalized distribution of labeled xylan-binding modules across cell walls on Scots pine (Pinus sylvestris) wood sections.…”
mentioning
confidence: 99%
“…These are alternatives to antibody probes because they are smaller (e.g. typically <20 kDa vs. ~150 kDa for antibodies) and show specificity for individual carbohydrates (Ding et al 2006;Filonova et al 2007b;Oliveira et al 2015;Pattathil et al 2015). Furthermore, the ease of their production and modification with peptides and fluorescent and gold markers for microscopy is also encouraging (Filonova et al 2007b).…”
Section: Introductionmentioning
confidence: 99%
“…Cellulose in wood fibre cell walls has been localised by CBMs (Mclean et al 2002;Hildén et al 2003;Daniel et al 2006;Ding et al 2006;Filonova et al 2007a), such as xylan (McCartney et al 2006;Filonova et al 2007b), and mannan (Filonova et al 2007a). McCartney et al (2006) studied the affinity of six different xylan-specific CBMs in binding to primary and secondary cell walls for several dicotyledonous species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation